Geeeeente, me ajudem nessa questão?
Anexos:
![](https://pt-static.z-dn.net/files/dee/39be95bf1cecbe4f43057f2ff620369b.jpg)
Soluções para a tarefa
Respondido por
0
A = √9x
B = 2√100x
C = -8√36x
===
A - (B + C)
√9x - (2√100x + (-8√36x))
√9x - (2√100x -8√36x)
3√x - (2.10√x - 8.6√x)
3√x - (20√x - 48√x)
3√x - (-28√x)
3√x + 28√x
=> 31√x
B = 2√100x
C = -8√36x
===
A - (B + C)
√9x - (2√100x + (-8√36x))
√9x - (2√100x -8√36x)
3√x - (2.10√x - 8.6√x)
3√x - (20√x - 48√x)
3√x - (-28√x)
3√x + 28√x
=> 31√x
Perguntas interessantes
Geografia,
10 meses atrás
Matemática,
10 meses atrás
Biologia,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás